2011
DOI: 10.12659/msm.881921
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of a variety of thermal and vibratory modalities on skin temperature and blood flow in healthy volunteers

Abstract: SummaryBackgroundCirculation plays an essential role in tissue healing. Moist heat and warm water immersion have been shown to increase skin circulation; however, these heating modalities can cause burns. Recent research has shown that passive vibration can also increase circulation but without the risk of burns.Material/MethodsThe aim of this study is to compare the effects of short-duration vibration, moist heat, and a combination of the two on skin blood flow (SBF) and skin temperature (ST). Ten (10) subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
0
47
1
Order By: Relevance
“…Only 7 studies reported the experiment room temperature which ranged between 21 and 25°C (Hazell et al ., ; Lohman et al ., ; Lohman et al ., ; Lohman et al ., ; Manimmanakorn et al ., ; Seixas et al ., ; Sonza et al ., ). An adaptation period of 5 (Lythgo et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7 studies reported the experiment room temperature which ranged between 21 and 25°C (Hazell et al ., ; Lohman et al ., ; Lohman et al ., ; Lohman et al ., ; Manimmanakorn et al ., ; Seixas et al ., ; Sonza et al ., ). An adaptation period of 5 (Lythgo et al .…”
Section: Resultsmentioning
confidence: 99%
“…For the included studies, we calculated the unweighted vibration acceleration level widely ranging between 2·46 m s −2 r.m.s. (Lythgo et al ., ) and 295·79 (Lohman et al ., ; Lohman et al ., ) m s −2 r.m.s. Among these studies, only 6 studies reported own‐calculated peak acceleration level for the applied vibration (Kerschan‐Schindl et al ., ; Lohman et al ., ; Lohman et al ., ; Lythgo et al ., ; Manimmanakorn et al ., ; Menéndez et al., ); we observed a large discrepancy between the levels of the reported vibration acceleration and our calculated vibration acceleration for those studies except the studies by Kerschan‐Schindl et al .…”
Section: Resultsmentioning
confidence: 99%
“…This result is in consonance with other studies in which the vibration stimulus alone (50 Hz, 5-6 mm) was not sufficient to increase the ST after 10 min of application in healthy individuals. 20,35 Interestingly, despite no change in ST, a 10-min bout of WBV (26 Hz -6 mm) increased muscle temperature by 1.5°C in young adults. 36 However, in previous studies, 35,37 vibration applied directly to the skin surface of the resting extremity (passive vibration) was effective to increase skin blood flow and ST against standing on the platform (active vibration).…”
Section: Combined Therapy In Spinal Cord Injurymentioning
confidence: 95%
“…20,35 Interestingly, despite no change in ST, a 10-min bout of WBV (26 Hz -6 mm) increased muscle temperature by 1.5°C in young adults. 36 However, in previous studies, 35,37 vibration applied directly to the skin surface of the resting extremity (passive vibration) was effective to increase skin blood flow and ST against standing on the platform (active vibration). Of note, a large area of the extremity directly exposed to passive vibration may account for the local increase in ST.…”
Section: Combined Therapy In Spinal Cord Injurymentioning
confidence: 95%
“…Moreover, although hot water appears to be an effective treatment for pain [71], its use might be questionable, as the greatest hazard from C. fleckeri venom is a cardiotoxin [32,62]. Since the latter toxin can be carried directly and quickly into the circulatory system, applied heat may increase the blood flow, therefore resulting in increased severity of the cardiotoxic effects [72]. Carrette [70] appropriately concluded that if the sting is minor or unnoticed and systemic symptoms have already developed, heat application may be useless.…”
Section: 2 Cubozoans Speciesmentioning
confidence: 99%